Between the cloister and the agora: structural tensions and the political potential of university extension in Ancient History in contesting public uses of the past - Furlani, João Carlos (Guará Journal, 2025)
Contemporary Brazilian universities operate under the constitutional principle of the inseparability of teaching, research, and outreach. However, the daily reality of higher education institutions reveals a persistent asymmetry in this three-pronged approach. This article critically examines the peripheral position of university extension in the field of History in Brazil, with specific focus on Ancient History. Drawing on a sociological analysis of the academic field, it argues that the low institutionalization of extension practices does not result merely from operational deficiencies, but from structural factors: a system of academic distinction centered on bibliographic productivity, a disciplinary culture that historically divorced erudition from public mediation, and evaluation mechanisms that penalize extension work. In contrast, the article contends that extension–understood not as dissemination according to the "deficit model," but as dialogical interaction and shared authority–is a condition for social responsibility and epistemological renewal of the discipline. Grounded in the theory of historical consciousness, Public History, and Classical Reception Studies, the work proposes a typology of extension practices and a replicable program design for Ancient History, aimed at contesting public uses of the past and expanding historical literacy in contexts of democratic crisis and political instrumentalization of Antiquity.
Keywords: University extension; Teaching Ancient History; Public history; Classical reception; Uses of the past